Axial length to corneal curvature radius ratio is negatively correlated with choroidal blood flow in myopic children - Ye, Yurong; Hu, Zizhong; Su, Na; Shen, Yeyu; Yuan, Songtao (Frontiers in Ophthalmology, 2025)
BackgroundThe pathophysiologic mechanisms underlying early-onset myopia remain unclear; in this study, we investigate the pathogenesis by examining the interrelationships between axial length to corneal curvature radius ratio (AL/CR) and choroidal blood flow.MethodsThis cross-sectional study included 202 eyes from myopic children, categorized into 141 eyes with mild myopia, 47 eyes with moderate myopia, and 14 eyes with high myopia. Optical coherence tomography angiography (OCTA) was used to measure choroidal blood flow perfusion within a 6 mm × 6 mm area of the macular region, divided into nine subareas based on ETDRS partitioning: macular fovea, nasal side 1, superior 1, temporal side 1, inferior 1, nasal side 2, superior 2, temporal side 2, and inferior 2. Data on corneal curvature and ocular axial length were collected to calculate the AL/CR, with equivalent spherical lens power, gender, and age gathered for group comparisons, and the correlation between AL/CR and choroidal blood flow perfusion volume was analyzed.ResultsAL/CR was significantly negatively correlated with choroidal blood flow perfusion (P<0.001). Linear regression and mediation analyses indicated that for each unit increase in choroidal blood perfusion volume in nasal region 1, AL/CR decreased by an average of 0.421 units. This relationship is mediated by several factors, with axial length serving as a key mediator.ConclusionAL/CR correlates with choroidal blood flow perfusion, indicating a link between refractive biological parameters and ocular blood circulation. Myopia is an ischemic eye condition that warrants attention to fundus microcirculation changes in myopic children.